Study on infestations and biodiversity of metazoan parasites in Channa punctatus (Bloch), Mymensingh region: Infestation and biodiversity of metazoan parasites (Journal of the Bangladesh Agricultural University, 2019)
An investigation was conducted on infestation and reviewed biodiversity of metazoan parasites in Channa punctatus of Mymensingh region from July 2013 to June 2014. A total of 235 fish were examined and 9 species of four groups of parasites were recorded. They were (i) Euclinostomum multicaecum Tubangui and Masilungan, 1935 (ii) Euclinostomum heterostomum (Rudolphi, 1809) (iii) Genarchopsis goppo Ozaki, 1925 (iv) Allocreadium handiai  Pandey, 1937 (v) Senga ophiocephalina (Tseng, 1933) (vi) Porrocaecum sp. (vii) Ascaridia sp. (viii) Contracaecum sp. (ix) Pallisentis ophiocephali (Thapar, 1930).The maximum (86.67%) prevalence was found in  (86.67%) October and minimum (35.00%) in December whereas the maximum mean intensity (10) was observed in June and the minimum (1.42) was recorded from December. The prevalence was observed higher (68.85%) in smaller size of fish and in case of larger fish the prevalence was lower and the value was (53.62%). On the other hand, the mean intensity (5.45) was higher in smaller fish and lower (3.39) in medium sized fish. Both prevalence and mean intensity was found maximum in female fish than male fish. Among the four groups of parasites, infestation of Digenetic trematode is much higher than Nematoda, Cestoda and Acanthocephala. During the study, a list of parasites reported from Channa punctatus of Indian sub-continent was prepared. It was found that 38 species of Digenea, 4 species of Cestoda, 26 species of Nematoda and 5 species Acanthocephala were recorded. The Biodiversity of parasites seemed to be declined day by day. The responsible factors for this declination may be environmental degradation, entry of exotic fish and modernization of aquaculture etc.J Bangladesh Agril Univ 17(3): 409–416, 2019